Lamellar structured CoSe2 nanosheets directly arrayed on Ti plate as an efficient electrochemical catalyst for hydrogen evolution. (1st November 2016) - Xiao, Huaqing; Wang, Shutao; Wang, Cong; Li, Yanyu; Zhang, Hongrong; Wang, Zhaojie; Zhou, Yan; An, Changhua; Zhang, Jun
Highlights: DETA controlled growth of lamellar structured CoSe2 nanosheet. Direct growth of lamellar structrued CoSe2 nanosheets on Ti plate. An efficient HER catalytic cathode. Direct growth affording fast electrode kinetics. Abstract: Splitting water by electrochemical reactions is considered to be the most promising strategy to create hydrogen. Herein, an efficient hydrogen evolution cathode was developed by in-situ growth of lamellar structured cobalt diselenide (CoSe2 ) nanosheets on the surface of commercial titanium (Ti) plate (CoSe2 NS@Ti) in the first time. Both SEM images and XRD data confirmed that the Ti plate is homogeneously coated by few stacking layers of lamellar structured CoSe2, which could provide more active sites for hydrogen evolution reaction (HER) with the thickness about 20 nm. This catalytic cathode shows exceptionally high activity for hydrogen evolution with 152 mV overpotential to afford a current density of 10 mA cm −2 and a high exchange current density of 5.01 × 10 −3  mA cm −2, as well as high cyclic stability with negligible decrease of cathodic current after 500 cycles. Remarkably, the CoSe2 NS@Ti catalyst exhibits fast hydrogen evolution kinetics with Tafel slope of 38.5 mV per decade, which approaches the state-of-art Pt catalyst (Pt/C) in 0.5 M H2 SO4 . This CoSe2 NS@Ti material is easily prepared with excellent electrocatalytic performance, thus could be a promising earth-abundant electrocatalyst for the HER and other renewable energy applications.